Blockade of the JNK Signalling as a Rational Therapeutic Approach to Modulate the Early and Late Steps of the Inflammatory Cascade in Polymicrobial Sepsis - Gabriele Pizzino; Alessandra Bitto; Giovanni Pallio; Natasha Irrera; Federica Galfo; Monica Interdonato; Anna Mecchio; Filippo De Luca; Letteria Minutoli; Francesco Squadrito; Domenica Altavilla (Hindawi Limited, 2015)
Cecal ligation and puncture (CLP) is an experimental polymicrobial sepsis induced systemic inflammation that leads to acute organ failure. Aim of our study was to evaluate the effects of SP600125, a specific c-Jun NH2-terminal kinase (JNK) inhibitor, to modulate the early and late steps of the inflammatory cascade in a murine model of CLP-induced sepsis. CB57BL/6J mice were subjected to CLP or sham operation. Animals were randomized to receive either SP600125 (15 mg/kg) or its vehicle intraperitoneally 1 hour after surgery and repeat treatment every 24 hours. To evaluate survival, a group of animals was monitored every 24 hours for 120 hours. Two other animals were sacrificed 4 or 18 hours after surgical procedures; lung and liver samples were collected for biomolecular and histopathologic analysis. The expression of p-JNK, p-ERK, TNF-α, HMGB-1, NF-κB, Ras, Rho, Caspase 3, Bcl-2, and Bax was evaluated in lung and liver samples; SP600125 improved survival, reduced CLP induced activation of JNK, NF-κB, TNF-α, and HMGB-1, inhibited proapoptotic pathway, preserved Bcl-2 expression, and reduced histologic damage in both lung and liver of septic mice. SP600125 protects against CLP induced sepsis by blocking JNK signalling; therefore, it can be considered a therapeutic approach in human sepsis.